Twoline Skiffia's Latency to Exit a Refuge and to Locate Food When Socialising With Invaders and Raising Temperatures - Abigail Santiago‐Arellano; Javier Alcocer; Erick de laBarrera; Morelia Camacho‐Cervantes (Ecology and Evolution)
ABSTRACT Aquatic ecosystems are reservoirs of biodiversity and are highly threatened. Among the main threats to biodiversity are invasive species and global warming, the later has allowed the establishment of invasive species from originally warmer climates outside their native range by reducing the barriers to their establishment and distribution. Behaviour is the immediate response that species modify to counteract changes in their environment. Latency to respond to certain stimuli is an indicator of different behavioural tendencies associated with boldness, for example, quickly leaving a shelter could lead to benefits like finding a mate or locating food faster. We investigated the latency to exit a refuge and to locate food of the native twoline skiffia (Skiffia bilineata) from central Mexico at three temperatures (18°C, 23°C and 28°C) and in the presence/absence of invasive guppies (Poecilia reticulata). Our results are the first to show native fish could benefit from associating with invaders when emerging from a refuge and locating food under higher temperatures, but they would find themselves at the extreme of their thermal tolerance. Evidence of positive outcomes from biological invasions is increasing; however, further research is needed to understand if potential benefits for natives are temporary, which may make biological invasions less detrimental during the initial stages.